Achieving the Exigency of Pattern Development Among Clothing and Textiles Students in Tertiary Institutions for Garment Production in South East, Nigeria - Juliana Ego Azonuche; Obioma Angela Adilo; Oghenetega Ichekor; Favour Emelie Afam-Osia (PT. Pusmedia Group Indonesia, 2025)
This study addresses the critical need to enhance pattern development skills among clothing and textiles students in tertiary institutions in South East, Nigeria. Focused on the context of large-scale garment production, both in rural and urban areas, the research explores the dynamic interplay between traditional craftsmanship and contemporary techniques within the local fashion industry. Three research questions guided the study and hypotheses tested at 0.05 significance level. The study adopted the ex-post facto research design using the descriptive survey method. The population of the study was 363 subjects, which comprised of all the Clothing and textiles students in Federal and State tertiary institutions in South East States. The research instrument used to collect data from the respondents was a structured questionnaire. The reliability of the questionnaire was determined with the use of Split-half reliability method. The data collected from respondents were coded and inputted in SPSS, Version 23, and analyzed with frequency counts, percentages, mean (¯X) scores, Standard Deviation (SD), Improvement Need Index (INI), and t-test statistical tools. The result showed that Students in clothing and textiles require improvement in eight competencies for pattern drafting, including the use of 3D and 2D digital scanner software. Nine competencies in pattern alteration and adaptation, such as developing construction plans and alter and adapt pattern pieces need enhancement. Additionally, 11 competencies in pattern grading, involving correct measurement application require improvement. Notably, there were no significant differences in mean performance or need ratings between students in Colleges of Education and Polytechnics, as well as between students in rural and urban areas. Investing in the education and training of clothing and textiles students, policymakers, educational institutions, and industry stakeholders can contribute to skilled workforce development capable of driving innovation. The study advocates for strategic investments by policymakers, educational institutions, and industry stakeholders to ensure a well-prepared workforce. Bridging the gap between theory and application is paramount, and initiatives such as vocational training programs, industry-academia collaborations, and access to modern technology and nurture skills.